Electronic governance in Metro Iloilo e-commerce law implementation in the local level - Ramos, Sean E (Iloilo City University of the Philippines Visayas, 2009)
The advent of Information and Communication Technology (ICT) as a powerful tool that enable the effective and efficient delivery of products and services has redefined the fundamentals of governance. This paradigm shift has triggered the national government to pass the Electronic Commerce Act (RA8792) in 2000 to serve as the basis for the nationwide implementation of e-governance program. With this, it is crucial to find out how various government agencies through their respective key personnel perceive, design, implement, and monitor e-governance activities. This study aims to present and discuss the legal basis of the e-governance program, the various projects implemented by leading national agencies, the support of local officials, and the ICT capabilities of the LGUs to implement the program in order to achieve the goals of the E-Commerce Act. Thirty-six personnel from Metro Iloilo member-LGUs were chosen as respondents, six of which are IT officer/designate of their respective agency. Primary data were taken from survey questionnaires while secondary ones were obtained from various IT-related articles, books and journals and electronic copies downloaded from several websites. Results show that while respondents have mixed perception of how e-governance program is being implemented, they unanimously believe the importance of the initiative to the development of the country. It is also observed that the e-governance implementation in Metro Iloilo is far from satisfactory. Likewise, the problems presented demonstrate the inefficiency of LGU e-governance project implementers not to mention the deficiencies of the assisting national agencies. Lastly, as intended to call decision-makers for actions, recommendations are illustrated on the latter part.
Research Paper (M.M.) -- Iloilo City : University of the Philippines Visayas, 2009.
Keywords: Internet in public administration; E-commerce law -- Philippines -- Metro Iloilo area -- Law and legislation